Answer:
[tex](6)(-2)(-3)(1)(5)=180[/tex]
Step-by-step explanation:
We want to simplify the product:
(6)(-2)(-3)(1)(5)
Multiplying from right to left, we have:
[tex](6)(-2)(-3)(1)(5)=(6)(-2)(-3)(1*5)[/tex]
This gives us:
[tex](6)(-2)(-3)(1)(5)=(6)(-2)(-3)(5)[/tex]
[tex]\implies (6)(-2)(-3)(1)(5)=(6)(-2)(-3*5)[/tex]
[tex]\implies (6)(-2)(-3)(1)(5)=(6)(-2)(-15)[/tex]
[tex]\implies (6)(-2)(-3)(1)(5)=(6)(-2*-15)[/tex]
[tex]\implies (6)(-2)(-3)(1)(5)=(6)(30)[/tex]
[tex]\implies (6)(-2)(-3)(1)(5)=(6*30)=180[/tex]